Studi Morfologi Tanaman Sansevieria Di Kota Makassar - Istiqamah, I.; Hiola, St. Fatmah; Karim, Hilda (bionature, 2018)
Abstract. This research is a descriptive study which aims to study the morphological characteristics of Sansevieria plants in Makassar City. This research was conducted from February to March 2018. The location of the study was conducted in several areas in Makassar city which Sansevieria met. Data collection was done by observing the morphological characteristics of Sansevieria plants. The results of the study obtained as many as 25 species of Sansevieria. Sansevieria plants in the city of Makassar are dominated by species with dark green to gray green, only a few are pale green or have a combination of yellow, have a shape or build a variety of leaves such as wake oval (ovalis), elongated (oblongus), lancet (lanceolatus ), to subulate or terete (subulatus).Keywords: Sansevieria, Characteristics, Morphology, Makassar City.